2018
DOI: 10.1002/adma.201705078
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Nucleic Acid Chemistries: Combining the Best of Both Worlds to Construct Advanced Biomaterials

Abstract: Hybrid synthetic amphiphilic biomolecules are emerging as promising supramolecular materials for biomedical and technological applications. Herein, recent progress in the field of nucleic acid based lipids is highlighted with an emphasis on their molecular design, synthesis, supramolecular properties, physicochemical behaviors, and applications in the field of health science and technology. In the first section, the design and the study of nucleolipids are in focus and then the glyconucleolipid family is discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 99 publications
(131 reference statements)
0
38
0
Order By: Relevance
“…In previous studies we explored the ability of hybrid nucleolipids 30 to form nanoparticles when formulated to different kinds of therapeutic molecules, including small active pharmaceutical ingredients (API) 31 , siRNA 32 , antisenses 33 . It was demonstrated that the resulting nanocarriers displayed higher biological activities compared to the unformulated drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we explored the ability of hybrid nucleolipids 30 to form nanoparticles when formulated to different kinds of therapeutic molecules, including small active pharmaceutical ingredients (API) 31 , siRNA 32 , antisenses 33 . It was demonstrated that the resulting nanocarriers displayed higher biological activities compared to the unformulated drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to produce more effective Ru(III)-based anticancer agents, able to cross the biological barriers, our research group proposed a prodrug approach. In this design, the active unit, AziRu, has been incorporated into highly functionalized nucleolipid-based scaffolds [101] able to form, under physiological conditions, stable self-assembling aggregates efficiently protecting the metal complex from biological degradation and conveying it through the cell phospholipidic bilayers [77,79,[102][103][104][105][106][107][108][109].…”
Section: Nucleolipid and Aminoacyl Lipid-based Structures Incorporatimentioning
confidence: 99%
“…[19,20] Whereas the main biological role of nucleic acidsi st os tore and process genetic information, lipids are key structurale lementso fm embranes,a sb oundaries that allow the compartmentalizationo fc ellular processes. Merging the properties of nucleic acids or their molecular componentsw ith that of lipids has therefore attracted much attention in recent times, [21] mostlyf or the design of artificial molecular devices [22,23] and varioust herapeutic strategies. [24,25] Herein, we showapossible use of nucleolipids in the context of systems chemistry,t oa chieve control of the self-assembly of lipidic amphiphiles, either pure or in mixtures, leading to different self-assembled nanoand microstructures as af unctiono ft he sequence of nucleobases present in the nucleolipid system.M oreover,s ome of the structures obtained in this work can encapsulate hydrophobic molecules, revealing ap otential as delivery vehicles of hydrophobic drugs or as compartmentst oh ost interesting chemistries in their interior.…”
Section: Introductionmentioning
confidence: 99%